SISTEM INFOMASI PENYEWAAN LAPANGAN OLAHRAGA MENGGUNAKAN METODE WATERFALL PADA GREEN GARDEN SPORT CENTER - -, Surtika Ayumida; -, Lukmanul Hakim; - Universitas Bina Sarana Informatika, Mohammad Syamsul Azis; - Universitas Nusa Mandiri, Chika Mahaulika (APMMI - Asosiasi Profesi Multimedia Indonesia, 2021)
Abstract - Today the world is familiar with internet-based technologies such as websites where all the desired information can be obtained easily. Green Garden Sport Center is still using a manual system in the field rental process. With the website of the Sports Field Rental Information System at the Karawang Green Garden Sport Center, it is expected to be able to assist customers in field bookings and assist in the data collection process. In building this system the author uses support tools with object-oriented methodology namely UML because UML supports the programming language of web applications, PHP and MySQL, while for writing PHP scripts the writer uses Sublime Text 3, the browser, functions to see the appearance of PHP commands that have been run on a web server. Examples of browsers are: Internet Explorer, Opera, Firefox, in designing this the author uses Mozilla Firefox. The system produced from the tools above will be far more optimal in terms of efficiency and effectiveness and easy to understand. With the creation of sports field rentals through the internet, it makes it easy for customers to determine schedules and find out information about available sports fields so that they do not experience schedule conflicts in managing field rentals, and can make it easier for administrators to manage field data, schedules and tenant data. Keywords : Information System, Sports Field Rentals Abstrak - Saat ini dunia telah mengenal teknologi berbasis internet seperti website dimana segala informasi yang diinginkan bisa diperoleh dengan mudah. Lapangan Olahraga Green Garden Sport Center masih menggunakan sistem manual dalam proses penyewaan lapangan. Dengan adanya website Sistem Informasi Penyewaan Lapangan Olahraga Pada Green Garden Sport Center Karawang diharapkan dapat membantu customer dalam pemesanan lapangan serta membantu dalam proses pendataan. Dalam membangun sistem ini penulis menggunakan alat pendukung dengan metodologi yang berorientasi objek yaitu UML karena UML mendukung bahasa pemrograman aplikasi web, PHP dan MySQL, sedangkan untuk penulisan script PHP penulis menggunakan Sublime Text 3, browser, berfungsi untuk melihat tampilan perintah-perintah PHP yang telah dijalankan di web server. Contoh browser yaitu: Internet Explorer, Opera, Firefox, dalam merancang ini penulis menggunakan Mozilla Firefox. Sistem yang dihasilkan dari tools diatas akan jauh lebih optimal dari segi efisiensi dan efektifitas serta mudah dipahami. Dengan dibuatnya penyewaan lapangan olahraga melalui internet ini, memudahkan bagi customer dalam menentukan jadwal dan mengetahui informasi tentang lapangan olahraga yang tersedia agar tidak mengalami bentrokan jadwal dalam pengelolaan penyewaan lapangan, serta dapat mempermudah admin dalam mengelola data lapangan, jadwal dan data penyewa. Kata kunci : Sistem Informasi, Penyewaan Lapangan Olahraga